Analisis Prinsip Pembiayaan Kesehatan dalam Mendukung Cakupan Kesehatan Semesta di Indonesia - Pribadi, Frita Ayu; Setijaningrum, Erna (Universitas Airlangga, 2023)
Health financing is an essential component of the health system, particularly in the pursuit of universal health care. The primary role of universal health care is financial risk protection, which includes the availability of national health insurance as well as access to safe and inexpensive essential health services. The goal of this study is to learn about the concepts of health financing in order to attain universal health care. This article employs a qualitative approach, drawing on secondary data sources such as books, scientific journals, linked internet websites, official government papers, and others. According to the findings, the effectiveness of raising income for health care finance cannot be quantified. In terms of income collection, there is still some overlap in health financing sources, particularly in the national health insurance programme (JKN). Aside from that, the JKN program's procurement of services and distribution methods are encountering difficulties due to a shortfall in the JKN budget, as well as the community's lack of discipline in making JKN contributions. Furthermore, despite the notion of decentralisation, local governments continue to rely on the central government for health financial planning and budgeting. Keywords: health systems, health financing, universal health coverage